El entorno familiar y su impacto en el proceso de aprendizaje de los estudiantes de quinto año A, B y C de la Unidad Educativa “Fe y Alegría” - Sangopanta Toaquiza, Geomayra Alexandra (2023)
The objective of this degree work was to determine the impact of the family environment on the learning process of fifth grade A, B and C students of the "Fe y Alegría" Educational Unit in the 2022-2023 school year. The methodology of this study adopted a mixed approach with a non-experimental design, the population with the respective sample was established considering the aforementioned school period, courses and parallels of the Educational Unit in question. First, the APGAR test was applied to identify family functionality, which evaluates five basic family functions: Adaptation, Participation, Gradient of resources, Affectivity and Resolving Capacity. Subsequently, the learning process was evaluated considering three aspects: Procedural, Attitudinal and Conceptual. Excel statistical software was used to process the data, with which tabulations, graphs and certain statistics were calculated in order to be able to perform the respective analysis. The results show that the vast majority of students have normal family functionality and only a small percentage of them live in a family with severe dysfunction. On the other hand, the three evaluated aspects of the learning process show favorable results, being the conceptual knowledge where this assertion is most evident, since all students reach and master the required learning. Therefore, it can be assumed that the family environment influences the learning process of fifth grade A, B and C students of the "Fe y Alegría" Educational Unit in the 2022-2023 school year. It is appropriate that educational institutions apply this type of test (APGAR) to their students periodically in order to verify that the family environment is appropriate for the proper development of children.